Possibilities of Ecotourism Development in Rani Mahal Area, Palpa, Western Nepal - Rai, Raju; Bhatta, Kabindra; Lamichhane, Mani Raj; Sharma, Sunil; Regmi, Dhananjay (Himalayan Review, 2024)
Nepal has significant potential for tourism due to its diverse flora and fauna, rich culture, and abundance of mountains, historical sites, and religious places. This study assesses the potential for ecotourism development in the Rani Mahal area of Palpa district. The research was based on Focus Group Discussions (FGDs), Key Informant Interviews (KIIs), and field observations. In total, FGDs were conducted in five locations, and 38 KIIs were carried out. The study found that ecotourism activities such as white-water rafting, beach volleyball, homestays, and hiking are feasible in the Rani Mahal area. White-water rafting in the Kali Gandaki River (from Ridi to Ramdi) and beach volleyball in the Rani Mahal area were identified as highly promising for ecotourism. Similarly, homestays in Bote village (Dailathun) and Satuka (Syangja) were also found to have high potential. Additionally, hiking routes from Rani Mahal to Magar homestay (Baugha Gumha), Alamdevi temple (Syangja), Argali, and Ridi offer great potential for ecotourism activities. The results of this study provide valuable insights into tourism planning, infrastructure development, and the sustainable development of ecotourism in the Rani Mahal area.